KOLABORASI DALAM PENGELOLAAN SAMPAH DI KOTA CIREBON - Nurhanifah, Alisa; Rostyaningsih, Dewi; Warsono, Hardi (Journal of Public Policy and Management Review, 2024)
This research is based on the phenomenon that collaboration of waste management in Cirebon has not been effective. The aim of this research is to analyze collaboration in waste management in Cirebon and analyze the supporting and inhibiting factors for collaboration in waste management in Cirebon. The research was conducted by using qualitative methods with descriptive analysis. Data collection was conducted from interviews, observations and documentation. Data analysis was conducted by using qualitative analysis which included three activities which are reduction, data presentation, and verification and drawing conclusions. Meanwhile, data validity testing was conducted by using triangulation techniques. The results of the research are that collaboration in waste management seen from the aspects of input, process and outcomes has not been effective. From the input aspect, namely the lack of commitment of stakeholders to collaborate and the limited budget and infrastructure for waste management. From the process aspect, there are not many stakeholders who collaborate in waste management and there are still many RW heads who are less active in the waste bank program. From the outcomes aspect, the number of waste management facilities and infrastructure from collaboration has not been able to create optimal waste management, waste reduction has not been able to reach the target, and the improvement in the quality of waste management has not been significant. There are supporting factors in the form of the availability and clarity of laws and regulations and the availability of programs in the environmental field. The inhibiting factors are the lack of company awareness, the lack of implementation of rewards and punishments in the TJSL program, the limited facilities and infrastructure for transporting waste, and the difficulty in changing the mindset of the community regarding waste management. The recommendations given are that the Cirebon City Government needs to take a personal approach to the company, increase socialization to companies regarding their obligations in the TJSL Regional Regulation, be proactive by emphasizing the implementation of rewards and punishments, conduct ongoing socialization related to waste management to the community using simple language.